Optimized Electroless Ni-Cu-P Coatings for Corrosion Protection of Steel Rebars from Pitting Attack of Chlorides - MUKHOPADHYAY, Arkadeb; SAHOO, Sarmila (Engineering Transactions, 2021)
Structures, constructions and bridges in coastal areas are greatly affected by the corrosive attack of chlorides. This reduces their lifetime and leads to losses due to their maintenance. This study aims to improve the lifetime and corrosion-proof behavior of steel rebars in the saline environment (3.5% NaCl) by applying electroless Ni-Cu-P coatings with high corrosion resistance. Ni-Cu-P coating was deposited on Fe-600 steel rebars. The coating was deposited by varying bath condition parameters, such as concentration of nickel sulphate, sodium hypophosphite and copper sulphate. This led to a variation in Ni, P and Cu content, and finally, the optimal bath combination was obtained using the Taguchi-based grey relational analysis. For concentrations of 25, 10 and 0.3 g/l nickel sulphate, sodium hypophosphite and copper sulphate, enhanced corrosion resistance of the coated rebars could be achieved with 350 mV Ecorr and 0.4 μA/cm2 Icorr. At the same time, the bare rebars had Ecorr of -653 mV and Icorr of 11.7 μA/cm2.